Success and failure in the pursuit of college education of high achieving students of three towns of Zambales, 1951-1961 - Sales, Gervacio N. 1925- (s.n.], 1962)
This study is concerned with the determination of the environmental factors which affect the academic performance of 246 students. These environmental factors include economic factors, educational background of the parents, size of the family, roles of the school, and health factors.